ASPEK SOSIOLOGIS PERAN SERTA MASYARAKAT DALAM PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Suriansyah Murhaini (Jurnal Cakrawala Hukum, 2017)
Sociological aspect of society role in environmental management and protection is close related with law andsocial aspect. Environmental management and protection is demanded to develop a integrated system that hasto run obedient and consistent from central to regional. Government role in environmental management especiallyto determine priority, through consider ecological interest, which ended with political decision. Societyroleby individual, NGO or corporation is consequences from right of good and healthy environment thatcanimplemented in administrative procedure. That role is a legal procedure that can efficiently affect to thequalityand decision making process that related to environmental, so that the arrangement is needed toregulateadministratively. Transparency in environment management is really essential, whereas the role is acontinuityfrom transparency can form in objection before decision is made. In the position as society protector,governmentshould has good paradigm in relation with environment. The reflection is making an exact lawregulationand reflect environmental pro political will. The political will that writtenly formed can be saviorofcorrelation between human and environmental and the good comes back to them as well.